Produksi Film Pendek â€œLike And Dislike â€ Menggunakan Sistem Multimedia - Utomo, Pandu; Purnama, Bambang Eka; Urbani, Yunan Hepy (Speed - Sentra Penelitian Engineering dan Edukasi)
Abstract - Development of the University of Surakarta assessed memorable film monotonous, it does not result in the development of cinema that puts the educational aspect. Short Film Production "Like And Dislike" Using Multimedia System is a renewal in cinema at the University of Surakarta, combining elements of multimedia and educational themes that will produce a short film that appeals to students. The problem is how to make a short film production or cinema as an educative function, using a multimedia system that film at the University of Surakarta not impressed monotonous. The goal is to produce educational breakthrough in cinema at the University of Surakarta which convey positive information message. Benefits of this research is to provide inspiration and insight into the nuances of educational, as well as add to the literature in film at the University of Surakarta. The research methodelogy used is literature, Observation, Interview, Design and Implementation, Documentation. Formulation of cinema production step process consisting of Pre-Production, Production and Post Production. Short Film Production "Like And Dislike" Using Multimedia System is expected to be a reference and information in producing cinema or indie films as a function of education, as an evidence of the application of IT multimedia science. KeywordsÂ Â Â  : Multimedia, Cinema Production Â  Abstrak - Perkembangan perfilman Universitas Surakarta dinilai berkesan monoton, hal itu mengakibatkan tidak berkembangnya sinema yang mengedepankan aspek edukatif. Produksi Film Pendek â€œLike And Dislikeâ€ Menggunakan Sistem Multimedia merupakan pembaharuan dalam perfilman di Universitas Surakarta, menggabungkan antara unsur unsur multimedia dan tema edukatif sehingga akan menghasilkan suatu film pendek yangÂ  menarik bagi mahasiswa. Adapun masalahnya adalah bagaimanaÂ  membuat sebuah produksiÂ  sinema atau Film Pendek Â sebagai fungsi edukatif, dengan menggunakan sistem multimedia agar perfilman di Universitas Surakarta tidak berkesan monoton. Tujuannya untuk menghasilkan terobosan edukatif dalam perfilman di Universitas Surakarta yang menyampaikan pesan informasi positif. Manfaat penelitian ini Â adalah memberikan inspirasi dan wawasan bernuansa edukatif, serta menambah pustaka dalam perfilman di Universitas Surakarta. Metodologi penelitian yang digunakan adalah Kepustakaan, Observasi, Wawancara, Perancangan dan Implementasi, Dokumentasi. Perumusan langkah produksi sinema terdiri dari proses Pra Produksi, Produksi, dan Pasca Produksi. Produksi Film Pendek â€œLike And Dislikeâ€ Menggunakan Sistem Multimedia diharapkan dapat menjadi referensi dan informasi dalam memproduksi sinema atau film indie sebagai fungsi edukasi, sebagai suatu bukti penerapan ilmu IT multimedia. Kata kunciÂ Â  :Â Â Â  Multimedia, Produksi Sinema